THE EFFECT OF COACHING ON EMPLOYEE PERFORMANCE IN PT. PLN (PERSERO) DISTRIBUSI JAWA BARAT DAN BANTEN - Pratama, Handika Eka; Saragih, Rohmat (2020)
This study aims to determine the effect of coaching on employee performance at PT PLN (Persero) Distribusi Jawa Barat dan Banten. The method used in this study is quantitative with a type of descriptive research. Researchers use probability sampling with random sampling techniques, a sample of 72 employees from a total population of 259 employees with a significance level of 10%. The analysis technique used is simple regression analysis. The results of the descriptive analysis showed that the two variables from all dimensions obtained an average in the good category. Based on the results of simple regression analysis and hypothesis testing, it can be concluded that caoching has a positive and significant effect on employee performance